A PRACTICAL INSIGHT INTO TALENT SOURCING - Randhawa, Ishika; Damodaran, Deepa (International Journal of Research -GRANTHAALAYAH, 2025)
This report titled “A Practical Insight into Talent Sourcing” presents an overview of my one-month internship experience as a Human Resources Intern from 10th June 2025 to 10th July 2025. The internship provided an opportunity to gain firsthand exposure to the operational aspects of Human Resource Management, with a primary focus on talent sourcing and recruitment. The report highlights how theoretical HR concepts such as recruitment planning, candidate evaluation, and policy implementation are applied in real organizational settings. It discusses the various roles and responsibilities undertaken, including screening job applications, coordinating interviews, maintaining employee records, and preparing standard operating procedures. The challenges encountered—such as handling multiple recruitment processes and sourcing candidates for specialized roles—are analyzed along with practical recommendations for improvement. Furthermore, the report reflects on the skills and competencies developed during the internship, such as analytical thinking, communication, teamwork, and adaptability. It concludes by emphasizing how this internship experience served as a bridge between academic learning and professional practice, deepening my understanding of human resource management and strengthening my aspiration to pursue a career in talent acquisition and employee engagement.